How Expensive is Norway? : New International Relative Price Measures - Krajnyak, Kornelia; Tulin, Volodymyr (Washington, D.C. : International Monetary Fund, 2010)
In this paper, we derive two new measures of international relative prices for Norway. Developments in these new measures follow rather closely movements in the CPI-based real effective exchange rate through the 1990s, but diverge after 2000-suggesting that the costs of living in Norway relative to its trading partners have risen in the recent years more than the real effective exchange rate would indicate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet